Preparation of Graphene Oxide-Embedded Hydrogel as a Novel Sensor Platform for Antioxidant Activity Evaluation of Scutellaria baicalensis - Yan, Shuai; Yue, Yinzi; Zeng, Li; Su, Lianlin; Hao, Min; Zhang, Wei; Wang, Xiaopeng (Frontiers in Chemistry, 2021)
Antioxidation is very important in medicine and food. The current evaluation technology often has many shortcomings. In this work, we propose an improved electrochemical sensing platform for the evaluation of antioxidant activity. A hydrogel was prepared based on graphene oxide, zinc ions and chitosan. Zinc ions play a role as a crosslinking agent in hydrogels. The structure of chitosan can be destroyed by injecting hydrogen peroxide into the hydrogel, and the free zinc ions can diffuse to the surface of the electrode to participate in the electrochemical reaction. This electrochemical sensor can evaluate the antioxidant activity by comparing the current difference of zinc reduction before and after adding of antioxidant. With the help of graphene oxide, this hydrogel can greatly enhance the sensing effect. This proposed electrochemical platform has been successfully applied for evaluating the antioxidant activity of Scutellaria baicalensis with the comparison of 2,2-diphenyl-1-picrylhydrazyl-based traditional analysis technology.